Human Resources for Health Policies : A Critical Component in Health Policies - Dussault, Gilles (World Bank, Washington, DC, 2013)
In the last few years, increasing attention has been paid to the development of health policies. But side by side with the presumed benefits of policy, many analysts share the opinion that a major drawback of health policies is their failure to make room for issues of human resources. Current approaches in human resources suggest a number of weaknesses: a reactive, ad hoc attitude towards problems of human resources; dispersal of accountability within human resources management (HRM); a limited notion of personnel administration that fails to encompass all aspects of HRM; and finally the short-term perspective of HRM. There are three broad arguments for modernizing the ways in which human resources for health are managed: a) the central role of the workforce in the health sector; b) the various challenges thrown up by health system reforms; and c) the need to anticipate the effect on the health workforce (and consequently on service provision) arising from various macroscopic social trends impinging on health systems. The absence of appropriate human resources policies is responsible, in many countries, for a chronic imbalance with multifaceted effects on the health workforce: quantitative mismatch, qualitative disparity, unequal distribution and a lack of coordination between HRM actions and health policy needs. Four proposals have been put forward to modernize how the policy process is conducted in the development of human resources for health (HRH): a) to move beyond the traditional approach of personnel administration to a more global concept of HRM; b) to give more weight to the integrated, interdependent and systemic nature of the different components of HRM when preparing and implementing policy; c) to foster a more proactive attitude among human resources (HR) policy-makers and managers; and d) to promote the full commitment of all professionals and sectors in all phases of the process. The development of explicit human resources policies is a crucial link in health policies and is needed both to address the imbalances of the health workforce and to foster implementation of the health services reforms.